Evaluasi Prestasi Belajar Mahasiswa Fakultas Teknik Universitas Negeri Yogyakarta - Imam Muchoyar; Basrowi Basrowi; Bernardus Sentot Wijanarka; Sudiyanto Sudiyanto; Ariadi Candra Nugroho; Soeprapto Soeprapto; Ichda Cahyati (Faculty of Engineering, Universitas Negeri Yogyakarta, 2013)
The objectives of this study are: (1) to identify the subjects that have low scores contributing to the low grade point average (GPA) of the students and (2) to evaluate the reasons for the low academic achievement among the students. This study was conducted from May 2012 until September 2012. It was an evaluation study.The method used in this study was a comparative descriptive, by comparing the students’ GPA and the categories of the students’ achievement based on the Academic Regulations of Yogyakarta State University. In addition, the study also qualitatively compared the subjects in the departments which have low achievement. The population were all active students of Faculty of Engineering, YSU in the academic year of 2011/2012 who have scores of below B in more than 3 courses. To evaluate the students who had low GPA, it is used purposive random sampling. The method of data collection used documentation, interviews and questionnaires. The data was analysed using qualitative and quantitative descriptive analysis. The conclusions of this study were: (1) the subjects of the fields study had a very dominant contribution to low GPA of the students. The percentages of the field of study subjects having low achievement in bachelor and associate degree programmes were 84.2% and 87.7% respectively; (2) The reasons for low achievement of the students based on the students ‘point of view were: (a) the learning implementation aspects, especially from the lecturers (unclear teaching and explanation, inappropriate materials, excessive tasks and homework, the assessment process), (b) tight schedule and (c) the intrinsic factors of the students. The reasons based on lecturers ‘point of view were: (a) the students’ input (low motivation, low quality, laziness), and (b) inadequate learning facilities both in terms of quantity and quality.